Metode Balancing Jig Procedure pada Tab Elevator Pesawat Boeing 737-800 untuk Mengurangi Dampak Flutter - Lalu Giat Juangsa Putra; Dian Saputra; Achmad Zahir Saputra (JURNAL INTEGRASI, 2018)
Primary flight control in aircraft consist of aileron, rudder and elevator, secondary flight control consist of flaps, slats, spoiler and trim tab. Before aircraft in flight, the primary and secondary flight con trol must be confirmed in balanced condition. If in unbalanced condition, flutter will occur when aircraft in flight. Flutter is an aeroelasticity phenomenon, it is a vibration phenomenon that caused aircraft wings "flapping" like a bird.This is because combination from stiffness of the wing structure, aerodynamic, and inertia (weight) from the structure. To avoid the occurrence of flutter, balancing flight control should be done, one of them is elevator tab. Elevator tab often called trim tab in elevator. Trim tab is attached to elevator that located in horizontal stabilizer. It must be confirmed in balanced condition even though elevator tab is a secondary flight control. Balancing tab elevator is by jig method procedure, which is tab must be removed first. Whether the elevator is balanced or not are determined by the value of Tab Assembly Moment (TAM) which is the result gained from this research is 15.22 lbfinch and the tab can be said balance, because according to SRM boeing 737-800 the maximum TAM range is 15.48 lbfinch. If the research obtained a result more than 15.48 lbfinch, the tab must be returned to paint shop, decreasing the load weight from the tab by peeling paint coating. If the decreasing load weight from tab can't be done, the tab is considered "rejected", so it must be replaced with the new one.